Internal Quality Assurance System in Achieving Accreditation Scores for Islamic Religious Higher Education - Tarigan, Tetty Marlina; Zahara, Fatimah (Al-Hayat: Journal of Islamic Education, 2024)
This research explores contextual factors and operational dynamics of implementing the Internal Quality Assurance System (SPMI) at several State Islamic Universities in Indonesia, namely Syarif Hidayatullah State Islamic University (UIN) Jakarta, North Sumatra State Islamic University (UINSU), State Islamic University (UIN) Sjech M Djamil Djambek Bukittinggi, Syekh Ali Hasan Ahmad Addary State Islamic University (UIN) Padangsidimpuan, and State Islamic College (STAIN) Mandailing Natal. This type of research is qualitative with a multi-case study approach. Data collection includes documentation, field notes about process dynamics, observations and interviews with the Head of the Quality Assurance Institute (LPM) and Focus Group Discussions with stakeholders such as study program managers, lecturers, students, alumni and university auditors. The validity of the data is ensured through reliability checks, triangulation, member checking, and audit trails. The research results show that in-case analysis examines contextual factors and operational dynamics that are unique to each institution. Various universities are exploring variations in adherence to Total Quality Management (TQM) principles. UIN Syarif Hidayatullah Jakarta's transition to a paperless system through the SIQA application is an example of TQM principles by increasing efficiency and data management in the Internal Quality Audit (AMI) process. UIN Sjech M. Djamil Djambek Bukittinggi faces challenges in auditor capacity and role clarity, requiring organizational adaptation to increase AMI's effectiveness. Overall, this research contributes to the academic discourse regarding internal audit quality and underlines the importance of systems theory and organizational change theory in improving educational quality assurance practices in State Islamic Universities and Colleges.